2018
DOI: 10.6000/1927-5951.2018.08.03.1
|View full text |Cite
|
Sign up to set email alerts
|

Alpha Mangostin and Xanthone from Mangosteen (Garcinia mangostana L.) Role on Insulin Tolerance and PPAR-γ in Preclinical Model Diabetes Mellitus

Abstract: Objective: This research elaborated role of alpha mangostin and xanthone on insulin resistance and peroxisome proliferator–activated receptor (PPAR)-γ by measuring blood glucose level and PPAR- γ expression on adipocyte cell culture. Methods: Insulin tolerance test were conducted using male wistar rat divided into 9 groups, which were normal, control (D-Glucose induced only), glibenclamide, various doses of a-mangostin and xanthone (5, 10, 20 mg/kgbw). All group induced by D-glucose 3 g/kg orally 30 minutes la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Tey believe this was due to the increased expression of gamma P21activated kinase (PPAK-c). In adipocytes, PPAK-c regulates gene expression in insulin signaling and glucose metabolism [31].…”
Section: Protective Efects Of Mangosteenmentioning
confidence: 99%
“…Tey believe this was due to the increased expression of gamma P21activated kinase (PPAK-c). In adipocytes, PPAK-c regulates gene expression in insulin signaling and glucose metabolism [31].…”
Section: Protective Efects Of Mangosteenmentioning
confidence: 99%
“…Thus, PPAR isoforms were suggested to be a suitable molecular target to treat skin diseases with aberrated cell proliferation such as psoriasis and skin cancers (Kim et al, 2006;Sertznig et al, 2008;Ramot et al, 2015). Xanthone derivatives such as 2 were found to upregulate PPARγ expression in the preadipocytes in rat retroperitoneal tissue of insulin-resistant mice models following treatment with 5, 10 and 20 mg/kg of the xanthone (Ratwita et al, 2018).…”
Section: Peroxisome Proliferator-activated Receptors As a Target Of Xmentioning
confidence: 99%
“… 2018 ; Ratwita et al. 2018 ). Several studies have also revealed that α-MG has various beneficial effects, including improving IR by increasing the expression of GLUT-4 and PPARγ in cardiac muscle and adipocyte (Ratwita et al.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have also revealed that α-MG has various beneficial effects, including improving IR by increasing the expression of GLUT-4 and PPARγ in cardiac muscle and adipocyte (Ratwita et al. 2018 , 2019 ), and reduced hepatic steatosis by regulating mitochondria function and apoptosis (Tsai et al. 2016 ).…”
Section: Introductionmentioning
confidence: 99%